La natura urbana a Parigi Individualizzazione, rappresentazione e competizione globale - de Biase, Alessia (Sociologia del territorio, 2022)
Nature in the city represents a crucial topic in defining citizens' quality of life. With the rise of new climate and energy challenges aimed at greater environmental sustainability, this issue has taken a renewed centrality in the urban environment as well. Urban Nature in Paris is a text on the socio-political trends affecting urban space and its relationship with nature, here understood with reference to vegetalisation. Individualization, representation, and global competition are thus the main tendencies that characterize the processes and practices of urban greening. These trends are strongly linked, even if these links are not always evident and obvious. On the one hand there is individualization, conceived as a new scale within which we try to frame contemporary processes of citizen participation in the care of urban green space; on the other hand there is representation, as a means through which to capitalize on and valorize the fragmented and individualized actions of urban greening; and finally there is global competition, in which urban nature from a simple sphere of local public action, becomes an international political arena in which some cities seek to assume leadership. Starting with an analysis of the dynamics that have appeared in recent years in Paris, this volume seeks to make these trends visible, showing the emergence, evolutions, relationships, and consequences, of these processes of urban greening.